Assemblies of Mesoporous FAU-Type Zeolite Nanosheets - Inayat, Alexandra; Knoke, Isabel; Spiecker, Erdmann; Schwieger, Wilhelm (Angewandte Chemie International Edition, 2012)
Holey sheets: Nanosheet assemblies of FAU-type zeoliteX with intracrystalline mesopores are prepared (see picture). This material is synthesized by soft-templating and combines micro, meso, and macropores in a hierarchically interconnected manner.
Keywords: hierarchy; mesoporous materials; nanosheets; soft templating; zeolites

Controlling morphology and optical properties of self-catalyzed, mask-free GaN rods and nanorods by metal-organic vapor phase epitaxy - Tessarek, C.; Bashouti, M.; Heilmann, M.; Dieker, Christel; Knoke, Isabel; Spiecker, Erdmann; Christiansen, S. (Journal of Applied Physics, 2013)
A simple self-catalyzed and mask-free approach will be presented to grow GaN rods and nanorods based on the metal-organic vapor phase epitaxy technique. The growth parameter dependent adjustment of the morphology of the structures will be discussed. Rods and nanorods with diameters reaching from a few mu m down to 100 nm, heights up to 48 mu m, and densities up to 8.10(7) cm(-2) are all vertically aligned with respect to the sample surface and exhibiting a hexagonal shape with smooth sidewall facets. Optical properties of GaN nanorods were determined using cathodoluminescence. It will be shown that the optical properties can be improved just by reducing the Ga precursor flow. Furthermore, for regular hexagonal shaped rods and nanorods, whispering gallery modes with quality factors up to 500 were observed by cathodoluminescence pointing out high morphological quality of the structures. Structural investigations using transmission electron microscopy show that larger GaN nanorods (diameter > 500 nm) contain threading dislocations in the bottom part and vertical inversion domain boundaries, which separate a Ga-polar core from a N-polar shell. In contrast, small GaN nanorods (similar to 200 nm) are largely free of such extended defects. Finally, evidence for a self-catalyzed, Ga-induced vapor-liquid-solid growth will be discussed. (C) 2013 AIP Publishing LLC.